Bioaccumulation, alterations of metallothionein, and antioxidant enzymes in the mullet Mugil cephalus exposed to hexavalent chromium. Issue 1 (December 2016) - Min, Eun; Ahn, Tae; Kang, Ju-Chan
Abstract A laboratory experiment was conducted to determine hexavalent chromium (Cr6+ ) accumulation in the mullet and investigate Cr6+ toxicity using a panel of biomarkers including metallothioneins (MTs), glutathione (GSH), glutathioneS -transferase (GST), and superoxide dismutases (SODs) for 4 weeks. Cr6+ bioaccumulation in all tissues, except muscle, was consistently time- and dose-dependent. The accumulation of Cr6+ for 4-week exposures was in the following order: kidney ≈ liver > intestine ≈ gill > spleen > muscle. Compared with the control, Cr6+ bioaccumulation was increased in ≥200 μg L−1 groups (P  < 0.05). An independent relation was observed between accumulation factors (AFs) and exposure concentration. But AFs increased with exposure time. In the liver and gill, GST and SOD differed from the control at a high Cr6+ concentration at 2 and 4 weeks (P  < 0.05). This study indicated that the gills were as sensitive as the liver to Cr6+ toxicity. However, the latter appeared to influence largely on the organism's adaptive response to Cr6+, since Cr6+ may elevate GSH and MT levels by enhancing the hepatic uptake of metal in the mullet.